An Evaluation of the National Greening Program Implementation in Simala, Cebu Philippines Utilizing ABCD Model - Abella, Rongie C.; Cutamora, Jezyl C. (European Scientific Journal, ESJ, 2019)
This descriptive-evaluative study is an evaluation of the effectiveness of the implementation of the National Greening Program in Simala National High School, a secondary public school in Cebu, Philippines utilizing the ABCD model. It identified the congruences and discrepancies of the intents and actualities of the following components: A - the participants, B - programs and operations, C - effects, and D - the social impact. It was revealed that for component A, 63.83 % of the target participants cooperated in the program activities. Component B evaluation showed that most of the objectives to operate the program based on DepEd Order No. 5, s. 2014 were achieved with just minor discrepancies. For component C, the following themes encapsulate the effects of the program to the participants which are “points for the effort”, “complied as required”, “green advocates”, and “environmental champions”. While the themes “disaster mitigation” and “fighting malnutrition” as the program’s social impacts assessed in component D were attained. Thus, the school effectively implemented the program in one school year. Planning ahead the schedule of activities through proper channeling of information and strictly requiring all target participants to attend are advisable. Coordinating with the proper office in setting up the seed bank facilities and forging more partnerships with the concerned public and private agencies are recommended to further minimize the gap between the intents and actualities.